2022
DOI: 10.1021/acsomega.2c04697
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Perfluorocarbon Liquids Cytotoxicity Tests: Direct Contact Versus the Test on Liquid Extracts

Abstract: The purpose of this study is to compare the in vitro cytotoxicity tests according to the ISO 10993-5 (2009) standards using direct contact and the test on liquid extracts of compounds previously identified as possible toxic impurities in perfluorocarbon liquids (PFCLs) for use in vitreoretinal surgery. Compounds including perfluorooctanoic acid (PFOA), 1H-perfluorooctane (1H-PFO), 2H-tridecafluoro-2-methylpentane, 1H,2H-octafluorocyclopentane, and 2H,3H-decafluoropentane were analyzed by 19 F NMR before and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Nevertheless, some researchers argued that based on the norms and recommendations of ISO 10993-5 (2009), the only reliable method to detect any potential cytotoxicity of PFCLs is by direct contact, not liquid extracts. Since testing of liquid extracts may not detect toxic impurities insoluble in water due to the incompatibility of PFCLs with aqueous solutions, which may lead to false negative results [30] . Moreover, some scholars raised questions regarding the validity of cytotoxicity test methods currently employed to certify the safety of PFO lots, and proposed new cytotoxicity test methods for volatile substances [31] .…”
Section: Perfluoro-n-octane In Retinal Detachmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, some researchers argued that based on the norms and recommendations of ISO 10993-5 (2009), the only reliable method to detect any potential cytotoxicity of PFCLs is by direct contact, not liquid extracts. Since testing of liquid extracts may not detect toxic impurities insoluble in water due to the incompatibility of PFCLs with aqueous solutions, which may lead to false negative results [30] . Moreover, some scholars raised questions regarding the validity of cytotoxicity test methods currently employed to certify the safety of PFO lots, and proposed new cytotoxicity test methods for volatile substances [31] .…”
Section: Perfluoro-n-octane In Retinal Detachmentmentioning
confidence: 99%
“…Consequently, the clinical need for PFCLs has therefore prompted production techniques improvement to purification. In addition, a coordinated effort must be made between researchers, clinicians, companies and health authorities to establish strict standards regulating manufacturing, purification and biosafety control requirements [30,32] . There are some limitations in our study.…”
Section: Perfluoro-n-octane In Retinal Detachmentmentioning
confidence: 99%
“…12,13 Although some adverse health effects have been reported in the latter application, 14 they have been attributed mainly to the presence of trace toxic impurities like non-fully substituted hydrocarbons and other derivatives. 15,16 However, although PFCs show high stability, it was recently found that they cause some environmental risks. 17 The compounds originally used for 19 F MRI are not watersoluble and have been used in the form of nano-or microemulsions which complicates some applications (e.g.…”
Section: Introductionmentioning
confidence: 99%